Use of a non-medicated plaster in chronic lumbar back pain: a randomized controlled trial - Ricci, Matteo; Mulone, Alessio; Elena, Nicholas; Vecchini, Eugenio; Valentini, Roberto; Gelmini, Margherita (Acta Biomedica Atenei Parmensis, 2022)
BACKGROUND:The latest technology on far infrared radiations reflects the radiations emitted by the human body and induces an antalgic and anti-inflammatory effect without active ingredients. Our primary aim was to assess pain level modifications throughout the treatment period with two different types of patches, compared to a placebo. As secondary aims, we focused on addressing patients’ quality of life and range of motion changes with each patch.METHODS: We assessed 54 patients with chronic lumbar back pain treated with FIT Therapy (far infrared technology) patch. Three different types of FIT Therapy patches (F4, F3, and placebo) were used according to the different power of action and patients allocated in a randomized fashion into the 3 arms of the study. Every single patient was assessed during the study using the VAS pain scale, the Roland Morris Disability Questionnaire for quality of life, and ROM for a total of 14 days.RESULTS: Only the F4 patch group significantly reduced pain level at T14 compared to the placebo group (p